Governance and Income Inequality (The Pakistan Development Review, 2006)
Major problems of developing countries are unequal income distribution and low growth rate, which affect their welfare aspects. It was implicitly assumed that whenever we achieve target of higher growth rate, benefit of growth would automatically trickle down to the poor. History of developing countries shows that the rich benefited more than the poor as evidenced by rising income inequality during the period of higher economic growth. The economic policy changes are often triggered by the logic of low level of equilibrium of output level, employment and income distribution. To overcome this low level of equilibrium trap, government often adopt polices so as to achieve high level of income and employment growth and development, and equitable income distribution. Coherent policy instruments are essential to meet these policy targets. Impact of any macro economic policy has been examined by studying its impact on economic growth and income distribution. In recent years polices have been directed toward reducing the level of poverty and inequality through raising quality of life in society by providing efficient and effective governance. This new economic philosophy has resulted in a massive change in the policy orientation of countries; the priority is now centred on issue of governance and focus is now shifted towards a qualitative nature of its growth and development. According to Sen (1983), the realisation of human capabilities, that enlarge the range of human choices, is essential for a broader notion and measure of economic well-being. The institutional frame work is then considered as one of the essential elements for translating growth and well-being into a sustainable process.